Defining the role of miRNAs regulated by the pluripotency gene NANOG in the development and progression of testicular germ cell tumours - Cardenas, Ryan (2018)
Testicular germ cell tumours (TGCTs) are the most common form of cancer diagnosed in young men in the developed world (Ferlay, 2010). The underlying mechanisms responsible for the development and progression of these tumours are not well understood. However, it is believed that in utero risk factors may contribute to the disease. TGCTs are believed to be derived from early stage primordial germ cells (PGCs) that failed to mature during embryonic development and remain in an immature state into adulthood (Almstrup et al., 2010; Novotny et al., 2012). Prior to the maturation process, PGCs express high levels of pluripotency factors, including the homeobox transcription factor NANOG (Yamaguchi et al., 2005; Irie et al., 2015). In addition to this, NANOG is highly expressed in TGCTs and amplifications of the NANOG locus is common in invasive TGCTs, suggesting a role in tumour malignancy (Clark et al., 2004). However, the function of NANOG in TGCTs remains still unknown. NANOG knockdown experiments in embryonic stem cells (ESCs) identified a key role for NANOG in promoting cell proliferation and pluripotency (Mitsui et al., 2003; Torres and Watt, 2008; Zhang et al., 2009). NANOG has also been shown to regulate microRNAs (miRNAs) that are key for the regulation of the cell cycle and differentiation of ESCs (Barroso-delJesus et al., 2008; Card et al., 2008; Marson et al., 2008).